2016
DOI: 10.1186/s12992-016-0200-x
|View full text |Cite
|
Sign up to set email alerts
|

The oral health of refugees and asylum seekers: a scoping review

Abstract: IntroductionImproving the oral health of refugees and asylum seekers is a global priority, yet little is known about the overall burden of oral diseases and their causes for this population.ObjectiveTo synthesize available evidence on the oral health of, and access to oral health care by this population.MethodsUsing a scoping review methodology, we retrieved 3321 records from eight databases and grey literature; 44 publications met the following inclusion criteria: empirical research focused on refugees and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
120
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(140 citation statements)
references
References 53 publications
(151 reference statements)
9
120
0
1
Order By: Relevance
“…However, recruiting participants from hard-to-reach and restricted populations is acknowledged to be rather difficult 15,52 . The sample was limited to refugees who were seeking dental treatment or a dental evaluation at the dental clinics in the camp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recruiting participants from hard-to-reach and restricted populations is acknowledged to be rather difficult 15,52 . The sample was limited to refugees who were seeking dental treatment or a dental evaluation at the dental clinics in the camp.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, which were mainly conducted in developed countries, demonstrated a higher burden of oral diseases and a negative perception of oral health among refugees compared with host residents [13][14][15][16][17] . Previous studies, which were mainly conducted in developed countries, demonstrated a higher burden of oral diseases and a negative perception of oral health among refugees compared with host residents [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…11, 12 The majority of refugees have lived in refugee camps before resettlement to a host country, and limited resources and stress during residence in refugee camps can lead to a variety of acute and chronic diseases that often persist upon resettlement. 14,15 Lack of access to dental services is costly, with an increased disease burden linking oral health and systemic conditions such as diabetes and cardiovascular disease that resulted in $2.7 billion of charges for dental-related emergency room visits across the U.S. between 2008 and 2010. 14,15 Lack of access to dental services is costly, with an increased disease burden linking oral health and systemic conditions such as diabetes and cardiovascular disease that resulted in $2.7 billion of charges for dental-related emergency room visits across the U.S. between 2008 and 2010.…”
Section: Oral Health Literacy Interventionmentioning
confidence: 99%
“…13 Initiatives have found that refugees are at high risk of poor oral health due to a number of factors, including lack of acculturated dietary intake, lack of access to oral health prevention and treatment before and after their arrival in their new country, lack of water fluoridation, and torture-related injuries to the mouth and face; and many refugee adults have never received dental care or been provided with access to common preventive measures such as a toothbrush. 14,15 Lack of access to dental services is costly, with an increased disease burden linking oral health and systemic conditions such as diabetes and cardiovascular disease that resulted in $2.7 billion of charges for dental-related emergency room visits across the U.S. between 2008 and 2010. 16,17 Immigrants, being mostly non-native English speakers and a vulnerable population, experience barriers to language, culture, and access to health care resources.…”
Section: Oral Health Literacy Interventionmentioning
confidence: 99%